Influence of surface treatment on shear bond strength of orthodontic brackets - Ione Helena Vieira Portella Brunharo; Daniel Jogaib Fernandes; Mauro Sayão de Miranda; Flavia Artese (Dental Press Editora, 2013)
INTRODUCTION: The shear bond strength of orthodontic brackets bonded to micro-hybrid and micro-particulate resins under different surface treatment methods was assessed. METHODS: Two hundred and eighty test samples were divided into 28 groups (n = 10), where 140 specimens were filled with Durafill micro-particulate resin and 140 with Charisma composite. In 140 samples, a coupling agent (silane) was applied. The surface treatment methods were: Phosphoric and hydrofluoric acid etching, sodium bicarbonate and aluminum oxide blasting, stone and burs. A Universal Instron Machine was used to apply an occlusal shear force directly to the resin composite bracket surface at a speed of 0.5 mm/min. The means were compared using analysis of variance and multivariate regression to assess the interaction between composites and surface treatment methods. RESULTS: Means and standard deviations for the groups were: Sodium bicarbonate jet 11.27±2.78; burs 9.26±3.01; stone 7.95±3.67; aluminum oxide blasting 7.04±3.21; phosphoric acid 5.82±1.90; hydrofluoric acid 4.54±2.87, and without treatment 2.75±1.49. An increase of 1.94 MPa in shear bond strength was seen in Charisma groups. Silane agent application reduced the Charisma shear bond strength by 0.68 Mpa, but increased Durafill means for bicarbonate blasting (0.83), burs (0.98) and stone drilling (0.46). CONCLUSION: The sodium bicarbonate blasting, burs and stone drilling methods produced adequate shear bond strength and may be suitable for clinical use. The Charisma micro hybrid resin composite showed higher shear bond means than Durafill micro particle composite.